2018
DOI: 10.3892/ol.2018.8596
|View full text |Cite
|
Sign up to set email alerts
|

53BP1 inhibits the migration and regulates the chemotherapy resistance of ovarian cancer cells

Abstract: Abstract. The major problems faced during the treatment of ovarian cancer are metastasis and the development of intrinsic or acquired drug resistance. The present study assessed whether tumor protein p53 binding protein 1 (53BP1) regulated migration and modulated chemotherapy resistance in SKOV3 cells and identified proteins associated with the molecular mechanisms underlying this coordinate regulation. SKOV3 cells were transfected using a 53BP1-expressing vector, which induced 53BP1 overexpression. The migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…23 Bcl-2 and Bax were confirmed to be related to the chemotherapy resistance in various tumors. 24 In our study, miR-23a inhibition was shown to suppress Bcl-2 expression but increase Bax expression, which was indicative of an accelerated OC cell apoptosis. Meanwhile, Oct-4, Nanog, and CD133 are known as stem cell markers and indicated as invasive and predictive markers in relation to a poor prognosis in oral squamous cell carcinoma (OSCC).…”
Section: Discussionsupporting
confidence: 52%
“…23 Bcl-2 and Bax were confirmed to be related to the chemotherapy resistance in various tumors. 24 In our study, miR-23a inhibition was shown to suppress Bcl-2 expression but increase Bax expression, which was indicative of an accelerated OC cell apoptosis. Meanwhile, Oct-4, Nanog, and CD133 are known as stem cell markers and indicated as invasive and predictive markers in relation to a poor prognosis in oral squamous cell carcinoma (OSCC).…”
Section: Discussionsupporting
confidence: 52%
“…The resistance of tumor cells to DDP allows cells to evade the cytotoxic effects of DDP, overcoming apoptosis (23); however, the underlying molecular mechanisms of DDP resistance require further investigation (24,25). miRNAs have been reported to be regulators of DDP resistance in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…This involves AKT translocating to the nucleus and becoming phosphorylated by DNA-PK, resulting in the inhibition of cisplatin-mediated apoptosis [ 52 ] ( Figure 2 ). A study has shown that the upregulation of 53BP1 in SKO3 ovarian carcinoma cells resulted in increased resistance to cisplatin [ 53 ] ( Figure 2 ). Finally, higher Ku70 expression is associated with a better response to cisplatin treatment and improved overall survival (OS) [ 54 ].…”
Section: Dna Repair Pathwaysmentioning
confidence: 99%